Seakeeping of a fast displacement catamaran - Dyachkov, Vasilij; Makov, Jurij (Transport, 2005)
The paper presents a complex method for the calculation of pitch and heave of a fast displacement catamaran. It incorporates speed factors, interference of catamaran hulls, stabilization factors and possibility to apply different stabilization cases including a stabilizer activation possibility. In the method the possibility to evaluate catamaran motions in irregular waves is also included. On the base of the presented method the computer program is developed and applied to calculate seakeeping characteristics of a catamaran stabilized with a fore passive wing. The results of calculation are in good compatibility with the experimental model tests of this catamaran in irregular waves. The calculation method could be effectively applied in the design stage of fast displacement catamarans or of fin stabilizers determining their effectiveness. First Published Online: 27 Oct 2010